Intensity and Rate of COVID-19 Infection in Pakistan - Anila Jaleel (ziauddin University, 2020)
Since the WHO has declared the Covid 19 pandemic, number of cases is on rise but not attained peak in Pakistan. Although people are affected by COVID-19 throughout the world but the impact of, the disease is different in various countries, which may be attributed to different factors1 . Scientifically it is point to ponder that though the official figures are in thousands but there may be many asymptomatic patients in our communities due to closed family living systems in Pakistan. There are more than 12 to 13 people living in single small apartments in Karachi, who are in so close contact with each other and the local transmission cannot be avoided in them. However, the positive thing is that the severity of disease and number of deaths in Pakistan are not as much as in developed countries. There could be a number of reasons, which are needed to be explored by researchers in Pakistan and world over.